Strategi Peningkatan Kinerja Pegawai Pada Perusahaan Jasa Bidang Elektrikal dan Mekanikal PT Jayabana Sinergi Utama: Employee Performance Improvement Strategy in The Electrical and Mechanical Services Company PT Jayabana Sinergi Utama - M. Fauzi Hidayat; M. Syamsul Maarif; Sekar Wulan Prasetyaningtyas (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Human Resource Management (HR) is an important element for the company. PT Jayabana Sinergi Utama (PT JSU) that has been established for more than two years, since December 2020, is a company that operates in electrical and mechanical services. PT JSU has not yet adopted or implemented the operations management well. However, the company was only run by the experience of the people involved which causes the optimality of the employee performance. Based on that problems, the purpose of this research was to see the factors or variables that influence the performance of PT JSU employees. The variables were taken are Compensation (X1), Competence (X2), Work Discipline (X3), Work Environment (X4) and Employee Performance (Y). Then, to determine the improvement strategy of employee performance, the authors used the analysist AHP method. The results of the SEM-PLS analysis test in this study indicate that the compensation, the competence, the work discipline, and the work environment directly influence the performance of PT Jayabana Sinergi Utama employees. While the best alternative to improve the employee performance based on the AHP analysis is by raising the status of the employees of the company. Keywords: ahp, employee performance, human resource management, work discipline, work environment